Kategorija tesnobe v kratki prozi - Jensterle-Doležal, Alenka (Primerjalna književnost, 2009)
The article compares the category of anxiety in the short prose of the Slovenian author Slavko Grum (1901-1949) and the German-Jewish author Franz Kafka (1983-1924) from Prague. Both of these expressionists can be understood as predecessors of existentialism. The metaphysical anxiety connected with the perception of time is part of the atmosphere of their narrative worlds.
Keywords: Grum, Slavko, 1901-1949; Kafka, Franz, 1883-1924; Slovene literature; slovenska književnost; nemška književnost; German-language literature; kratka proza; tematologija; tesnoba; primerjalne študije